Edukasi Pelajar Sebagai Pemilih Pemula Tentang Pentingnya Pemilu di Desa Pameungpeuk Garut - Purnama, Feri; Firmansyah, Muhamad Hilman (Jurnal Media Pengabdian Komunikasi, 2023)
Abstract First-time voters are those who will exercise their right to vote in an election for the first time. They may not have sufficient experience or knowledge about the electoral process, election participants including presidential candidates, legislative candidates, and DPD, as well as relevant issues on the election agenda. For this reason, it is important for novice voters to seek accurate and objective information before casting their votes in the election. General elections are a process of conducting elections democratically, which involves many citizens to elect their representatives in government or make important decisions to affect their country or region. This election education activity for novice voters coincides with the upcoming elections which will be held on February 14, 2024 simultaneously in all regions in Indonesia. The purpose of this community service is to provide education about the stages of the election so that they have insight and give their voting rights wisely. The material used is educational material for utilizing communication and information media to gain access to information about elections. The methods used are seminars and training in the form of lectures and direct practice to get information about elections. The results of this service to students as novice voters in Pameungpeuk Village are increasing knowledge and insights about elections. Students now know about elections and the importance of elections in this democratic country. Keywords: Education; elections; students; democracy.  Abstrak Pemilih pemula adalah mereka yang baru pertama kali akan menggunakan hak pilih mereka dalam pemilihan. Mereka mungkin belum memiliki pengalaman atau pengetahuan yang cukup tentang proses pemilihan, peserta pemilu baik calon presiden, calon legislatif, dan DPD, maupun isu-isu yang relevan dalam agenda pemilu. Untuk itu, penting bagi pemilih pemula mencari informasi yang akurat dan objektif sebelum memberikan hak suaranya dalam pemilu. Pemilihan umum merupajan proses dalam melaksanakan pemilihan secara demokratis yakni melibatkan banyak warga negara untuk memilih perwakilan mereka dalam pemerintahan atau mengambil keputusan penting untuk mempengaruhi negara atau wilayah mereka.  Kegiatan edukasi pemilu kepada pemilih pemula ini bertepatan dengan menjelang Pemilu yang akan dilaksanakan 14 Februari 2024 serentak di seluruh daerah di Indonesia. Tujuan pengabdian kepada masyarakat ini adalah untuk memberikan edukasi mengenai tahapan pemilu agar memiliki wawasan dan memberikan hak suaranya secara bijak. Bahan yang digunakan yaitu materi edukasi pemanfaatan media komunikasi dan informasi untuk mendapatkan akses informasi tentang pemilu. Metode yang digunakan yaitu seminar dan pelatihan berupa ceramah dan praktik secara langsung untuk mendapatkan informasi tentang pemilu. Hasil pengabdian kepada pelajar sebagai pemilih pemula di Desa Pameungpeuk ini semakin bertambahnya pengetahuan dan wawasan tentang pemilu. Pelajar kini telah mengenal tentang pemilu dan pentingnya pemilu di negara berdemokrasi ini. Kata-kata kunci: Edukasi; pemilu; pelajar; demokrasi.